2012
DOI: 10.1111/j.1472-765x.2012.03233.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial efficacy of the alkaloid harmaline alone and in combination with chlorhexidine digluconate against clinical isolates of Staphylococcus aureus grown in planktonic and biofilm cultures

Abstract: Aims:  To investigate the antimicrobial efficacy of an alkaloid, harmaline alone and in combination with chlorhexidine digluconate (CHG) against clinical isolates of Staphylococcus aureus (S. aureus) grown in planktonic and biofilm cultures. Methods:  Minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs) were determined for each micro‐organism grown in suspension and in biofilm using microbroth dilution method. Chequerboard assays were used to determine synergistic, indifferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…29 Staphylococcus aureus within a biofilm reportedly decreases the efficacy of chlorhexidine as a disinfectant. 30 A recent report suggests that S. pseudintermedius has the potential to form a biofilm. 31 Another explanation could be related to the fact that organic matter decreases the efficacy of disinfectants, including chlorhexidine.…”
Section: Discussionmentioning
confidence: 99%
“…29 Staphylococcus aureus within a biofilm reportedly decreases the efficacy of chlorhexidine as a disinfectant. 30 A recent report suggests that S. pseudintermedius has the potential to form a biofilm. 31 Another explanation could be related to the fact that organic matter decreases the efficacy of disinfectants, including chlorhexidine.…”
Section: Discussionmentioning
confidence: 99%
“…Xing et al (2012) evaluated the activity of the alkaloid harmaline against clinically isolated strains of S. aureus in combination with the antibiotic chlorhexidine. Their study found that harmaline is a relatively weak substance when confronted with strains tested in cells in suspension as well as in biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…Following incubation of the set plates at 37 uC for 24 h, the minimum biofilm inhibition concentrations (MBICs) were determined as the lowest concentration to show growth below or equal to that of the control. The minimum biofilm bactericidal concentrations (MBBCs) were identified as the lowest concentration demonstrating no bacterial growth (Hendry et al, 2009;Xing et al, 2012).…”
Section: Methodsmentioning
confidence: 99%